Pengawasan Pajak Reklame di Badan Pengelolaan Pendapatan Daerah Kota Bandung - irfan saeful ikhsan; Faizal Pikri (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
This research is motivated by the author's interest in the efforts of the Bandung City Regional Revenue Management Agency in monitoring the billboard tax. Based on the observations made, there is a problem, namely the advertisement tax revenue is not in accordance with the expected target due to the lack of direct implementation of the advertisement tax supervision, there are still taxpayers who put up billboards but do not report first, lack of human resources in monitoring the billboard tax supervision. in the Regional Revenue Management Agency. The research method used in this research is a qualitative approach with descriptive research type. Data collection techniques using through interviews, observation, documents and triangulation. The results of this study indicate that the advertisement tax supervision has implemented the characteristic theory of effective supervision. However, there are still dimensions that have not worked well, among others: in an organizational realistic dimension because the number of human resources under supervision is not sufficient. inhibiting factors, namely limited human resources, lack of awareness of taxpayers of local taxes, and the determination of the potential for advertisement tax that has not been on target. Efforts are made to monitor the billboard tax, namely increasing the number of human resources and increasing their competence through education and training, increasing the socialization of understanding about the billboard tax to the public, conducting periodic supervision of taxpayers so that there are no deviations or deviations. there are data errors submitted by taxpayers, and strict enforcement of the implementation of billboard tax supervision.